The Modernist and the Contemporary: A Graphological – Comparative Analysis of the Selected Poems of Emily Dickinson and Lang Leav - Ogayan, Hazel Chilion; Pedida, Jefferson Alberto (CV. Literasi Indonesia, 2024)
The purpose of this study is to conduct a stylistic analysis of the selected poems of Emily Dickinson, a 19th-century poet, and Lang Leav, a contemporary poet, focused on the graphological level of the poems. The researcher selected four poems by Dickinson and Leav as the literary texts to be analyzed. Using comparative stylistic analysis, the study aims to look for the graphological features woven in the poems of Dickinson and Leav. The graphological features in the selected poems were also compared to find any significant similarities and differences between the styles of the two poets considering that they belong to different periods. Lastly, the graphological features were analyzed to know their possible effect on the meaning of the poems. As a result, archaism, eye dialect, unconventional use of em dash and capitalization, inconsistent number of lines in each stanza, and inconsistent number of words in each line were found in the selected poems of Dickinson while Leav's selected poems contain eye dialect, diacritics, minimal use of punctuation, absence of capitalization, italics, and the inconsistent number of words in each line of the poems. It was also revealed that their graphological features have more differences than similarities and the effect of these graphological features in the selected poems is mainly for emphasis and to add to the visual elements of the literary texts.